Production and quality evaluation of cookies from composite flour of unripe plantain (Musa paradisiaca), groundnut (Arachis hypogaea L.) and cinnamon (Cinnamomum Venum) - Adegunwa, M.O.; Bamidele, B.O.; Alamu, Emmanuel Oladeji; Adebanjo, L.A. (Informa UK Limited, 2019)
The study evaluates the quality characteristics of cookies produced from unripe plantain, groundnut and cinnamon composite flour (PGC). PGC were mixed in varying ratios of 90:5:5, 85:10:5, 80:15:5, 75:20:5 and 75:25:5. 100% of wheat flour was used as control. All sample mixes were analyzed for proximate, functional, pasting and sensory qualities. The moisture, ash, fat, crude fiber, protein and carbohydrate contents of the cookies ranged from 4.91 to 5.72%, 2.21 to 3.34%, 17.61 to 20.24%, 46.60 to 57. 63%, respectively. The range of sensory scores for acceptance was significantly (P < .05) different. Cookies produced from plantain- groundnut- cinnamon (PGC) (70:25:5) was the most acceptable. However, cookies produced from composite flour were all accepted by the panelists. Addition of groundnut and cinnamon improved the nutritional contents of the cookies and this product could be consumed not only by children and youths but even by people with special dietary needs.